Antiproliferative Activity of Methanol Extract of Stachytarpheta Urticifolia (Salisb.) Sims Leaf on Human Cancer Four Different Cell Lines (Funded Work) - Sreelatha Regalagadda; Murali Mohan Challa (International Journal of Pharma and Bio Sciences, 2021)
Cancer represents one of the most serious health problems and major causes of death around the world. Many anticancer drugs in clinical use today are natural products or derived from natural sources. Stachytarpheta urticifolia is a herbal medicine widely distributed in many parts of the world. The antiproliferative activities of the methanolic extract of Stachytarpheta urticifolia leaves collected from Damuku rai village of Araku Valley near Ananthagiri Mandal in Visakhapatnam District, against HT-29, A-431, A-549 and Hep-G2 cell lines were investigated by using 3-(4,5-dimethyl thiazol-2-yl)-2, 5-diphenyl Tetrazolium Bromide (MTT) assay. The extract showed a strong antiproliferative activity against all cell lines with IC50 values of 20.89, 27.56, 38.45 and 49.65 at 250 μg/ml, respectively. Flow cytometry results showed that the extract arrested the cell cycle at S phase and the increase in the percentage of caspase 3 activity in HT-29 and the A-431 cells by 129.41% and 112.8 % respectively suggested that the extract could induce cell apoptosis by a caspase mediated pathway. These results demonstrated that the methanolic extract of Stachytarpheta urticifolia leaves collected from Damuku rai village has comparable strong antiproliferative activity. The research demonstrated that the Stachytarpheta urticifolia extracts from different parts of the plant had shown antiproliferative and induced Caspase-3 activity against the human cancer cell line. The findings of this study indicate that there is some justification for the use of Stachytarpheta urticifolia as anti-proliferative activity of Caspase-3 activity induced cell apoptosis by caspase mediated pathway.